Education, Globalization and the Nation State - Green, A. author. aut Link
IX, 206 p.
Keywords: Andy Green develops on his earlier historical work on Education and State Formation in a study of education and the nation state in an era of globalization. Education, Globalization and the Nation State offers the first sustained analysis of the implications of globalization for modern education systems. In a series of historical and comparative essays ranging from Europe to America and Asia, Green assesses the changing relations between education and the nation state in different regions, and concludes that the national education system is far from obsolete.